RELATIONSHIP BETWEEN THE CLAY COMPOSITION AND THE SOIL SOURCE IN WEST SUMATERA - Aidhia Rahmi; Helendra Helendra (Jurnal Penelitian Pendidikan IPA, 2019)
Clay mineral is widely used in ceramic materials, building materials, paper coating materials, catalyst support, and an alternative material for zeolite. This paper reports the study on the relationship between the position of soil (low and highland) and its mineral composition in Bukit Tinggi, West Sumatera, Indonesia. It was found that the lowland area indicates the existence of dominant kaolinite and mikasaite. Meanwhile the highland is characterized with dominant illite and kaolinite.Illite is the main component for ceramic. This due to the alkaline condition and high content of Al and K as well as high hydrothermal activity at high land presumably by volcanic activity.Keywords: clay mineral, XRD, XRF, kaolinite, illite-smectite